IMPLEMENTATION OF CHARACTER EDUCATION FOR PARTICIPANTS IN CLASS IV SDN 5 SINDANGKASIH - MUSTOIP, SOFYAN (Universitas Pendidikan Indonesia, 2018)
Students at this time, lack of polite attitude especially to teachers who should be respected. The sense of courtesy can be seen when the students shake hands with the teacher they meet, say